MICROCLIMATIC INTERFERENCE USING THE GREEN ROOF IN TROPICAL REGIONS, CASE STUDY IN CUIABÁ, MT - Rosseti, Karyna de Andrade Carvalho; Nogueira, Marta Crista de Jesus Albuquerque; Nogueira, José de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707702 This article aims to evaluating the interference of green roofs on microclimate of the builtenvironment, analyzing their potential in modifying the values of temperature and relativehumidity of the air surrounding the building. For this were used a prototype of 5m ², constructedof brick and cement, finished with plaster and roofed with fibre cement, where was installed thegreen roof. The prototype was monitored for 15 consecutive days of the summer and winterseasons, starting on February 5th, 2009 and ending on February 20th, 2009, between 8:00 a.m.and 6:00 p.m.. Were collected simultaneously data of relative humidity and air temperature in thesurroundings near the prototype and in a remote location, both presenting the same morphological characteristics. From the results it is concluded that the effects of green roof on themicroclimate are closely associated with the presence of water on the roof.